Pengaruh Pembiasaan terhadap Kesadaraan Diri dan Perilaku Prososial pada Anak Usia 4-5 Tahun di TK Khadijah Pandegiling Surabaya - RR Agustien Lilawati (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2019)
The development of early childhood is influenced by emotional social aspect. In the emotional aspect there is one part that affects the development of children is self-awareness. When the child knows of consciousness, then there is also a prosocial behavior. Based on the observation of early childhood (4-5 years) in Khadijah Pandegiling Surabaya kindergarten found that only 10 children have low self-awareness level and only 15 children have low prosocial behavior. Learning in Khadijah kindergarten in developing self-awareness and prosocial behavior can be done through habituation-habituation that aims to develop their own ability and survival. The aim of this study to determine the habit of self-awareness and prosocial behavior in early child aged 4-5 years in Khadijah Pandegiling Surabaya Kindergarten. This type of research is experimental research, with quantitative approach. The subjects of the study were TK A students in kindergarten Khadijah Pandegiling Surabaya.totaling 60 students. Data analysis technique used is Analysis of Variance (anova).The results of this study indicate that (1) Habituation effect on self-awareness in children aged 4-5 years in kindergarten Khadijah Pandegiling Surabaya; (2) Habituation effect on prosocial behavior in children aged 4-5 years in kindergarten Khadijah Pandegiling Surabaya; (3) Habituation effect on self-awareness and prosocial behavior in children aged 4-5 years in kindergarten Khadijah Pandegiling Surabaya.